Identification of cCMP- and cUMP-binding proteins using cCMP and cUMP coupled to agarose and biotin matrices - Sabine Wolter; Martin Neumann; Theresa Koenig; Tina Hagedorn; Frank Schwede; Andreas Pich; Roland Seifert (PLoS ONE, 2025)
There is increasing evidence for a role of cyclic CMP (cCMP) and cUMP as second messengers. In a recent study we showed that cCMP activates both purified cGMP-dependent protein kinase Iɑ (PKGIɑ) and cAMP-dependent protein kinase (PKA) isoenzymes with the regulatory subunits RIɑ and RIIɑ. PKARIɑ was identified as a cCMP-binding protein using cCMP coupled to agarose by immunoblotting and PKARIIɑ by MS analytic. In this study, we discovered PKARIɑ, PKARIIɑ and PKG as cCMP- and also cUMP-binding partners using cCMP- and cUMP-agarose. For the first time as well as cCMP and cUMP coupled to biotin matrices was used and from mouse lung tissue, A549 and HeLa cell lysates the identical proteins were also identified as cCMP and cUMP binding proteins. In proteomic approaches, three isoforms of PKG (PKGI, PKGIβ and PKGII) were identified as cCMP- and cUMP-binding proteins from mouse lung tissue. Here we show the binding of cCMP and cUMP to the most prominent target proteins PKA and PKG of the second messengers cAMP and cGMP. These results point to an impact for cCMP and cUMP as non-canonical second messengers in signal transduction pathways like cAMP and cGMP. Furthermore, the results show that the agarose matrices and also the cNMP botin matrices are excellent tools for identifying new binding partners for cCMP and cUMP.